2019
DOI: 10.1007/s11090-019-10033-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Jet–Target Interaction: Influence of Dielectric Permittivity on the Electric Field Experienced by the Target

Abstract: This work presents a study of the influence of dielectric permittivity on the interaction between a positive pulsed He plasma jet and a 0.5 mm-thick dielectric target, using a validated two-dimensional numerical model. Six different targets are studied: five targets at floating potential with relative permittivities r = 1, 4, 20, 56 and 80; and one grounded target of permittivity r = 56. The temporal evolution of the charging of the target and of the electric field inside the target are described, during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(70 citation statements)
references
References 52 publications
8
62
0
Order By: Relevance
“…We expect our electric field and temperature results to be valid for the interaction of non-thermal helium plasma jets with dielectric surfaces greater than 4 without a grounded plane in the vicinity. This has been shown numerically for the experienced electric field in a recent investigation 22 . The temperature of the target will vary with the volume of the dielectric, especially its thickness, because this determines how good the dielectric acts as a heat sink.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We expect our electric field and temperature results to be valid for the interaction of non-thermal helium plasma jets with dielectric surfaces greater than 4 without a grounded plane in the vicinity. This has been shown numerically for the experienced electric field in a recent investigation 22 . The temperature of the target will vary with the volume of the dielectric, especially its thickness, because this determines how good the dielectric acts as a heat sink.…”
Section: Discussionsupporting
confidence: 52%
“…This means that the studied plasma target interaction is characterized by this relatively high dielectric constant. Recent numerical work 22 has shown that the experienced electric field inside targets of 0.5 mm thickness at floating potential are similar when the dielectric constant is higher than 4. This means that the reported electric field values and patterns in this work could be comparable to the electric field which is experienced inside e.g.…”
mentioning
confidence: 99%
“…This depends on the dielectric properties of the sample and its thickness. It has been shown by modeling that the electric field obtained from the BSO target is comparable to other targets in the absence of grounded planes with similar thickness (0.5 mm) and a permittivity higher than 4 17 . When cold plasma jets are used for e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Although this information is important regarding the propagation of the ionization waves, it cannot be used for extrapolation to obtain what the target experiences since this is strongly dependent on the surface charges that are deposited on it 10 , 11 , 16 . Although a specific electro-optic target is used to study the induced electric field, numerical work 17 indicates that the induced electric field should be generally comparable to targets at floating potential with dielectric constant higher than 4 and a similar thickness of 0.5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The highly energetic noble gas molecules are subsequently expelled to the ambient air, reacting with oxygen and nitrogen to form reactive oxygen and nitrogen species, respectively [8]. With hundreds of chemical reactions taking place in the millisecond range, the redox chemistry in those plasma systems is highly complex and still subject to investigation [9,10]. Physical plasma treatment was shown to promote cell death in several tumor cell types, including skin cancer [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%